PENGATURAN SUDUT AZIMUTH ROKET RUM UNTUK OPERASI PELUNCURAN PADA KECEPATAN ANGIN DI ATAS 10 KNOT (AZIMUTH ANGLE’S SETTING OF ROCKET RUM FOR LAUNCH OPERATION AT WIND SPEED MORE THAN 10 KNOT) - Wibowo, Heri Budi; Riyadl, Ahmad; Nugroho, Yudha Agung (Indonesian Journal of Aerospace, 2016)
RUM rocket is a rocket used in the payload competition among university students. The rocket is designed to bring a maximum payload of 1 kg to altitude of 600-1000 m and falls safely on a 500 m radius of the left and right rear of the center point of the launching pad of the conditions of wind speeds below 10 knots. In extreme circumstances where the wind speed is above 10 knots, the effect of speed and direction of wind to the stability of the rocket flight direction large enough to cause it to fall beyond the defined safety radius. The research aims to adjust azimuth setting of the rocket so that the fall of the rocket motor remains secure within the radius of the launch area. The study was conducted by testing a rocket RUM in extreme conditions (wind speed of 10-20 knots) with variations in shear-pin and azimuth angle. The test variables are the position of the fallen rocket motor. The results show that the wind direction and speed significantly affecting direction of rockets flight. The results show that rocket azimuth angle of 60 degrees with the direction of 90 degrees from the wind direction can make thea rocket falls on a secure area (within 500 m).